REASONS TO ADOPT THE “COACHING LEARNING PROCESS” MODEL IN PERU UNIVERSITIES - Rodríguez del Solar, Octavia Natalia (2014)
The objective of this study is to present the need to generalize the "Orientation-Learning Process" in the country's universities, an active methodology is used, with the consequent incorporation of the components of this process: 1) The adult participant 2) andragogo or facilitator 3) the group of participants 4) community in conclusion, we achieved develop in man the consciousness of citizens to participate responsibly in the social, economic, political and cultural processes of the country.